2021
DOI: 10.3390/jcm10112249
|View full text |Cite
|
Sign up to set email alerts
|

Micro-RNA Analysis of Pancreatic Cyst Fluid for Diagnosing Malignant Transformation of Intraductal Papillary Mucinous Neoplasm by Comparing Intraductal Papillary Mucinous Adenoma and Carcinoma

Abstract: Although intraductal papillary mucinous neoplasm (IPMN) is thought to be a precursor lesion of pancreatic cancer, diagnosing malignant transformation of IPMN using non-invasive diagnostic methods is difficult and complicated. Micro-RNAs (miRNAs) are currently recognized as biomarkers and molecular targets of various diseases, including malignancy. In this study, we investigated a potential diagnostic approach using miRNA in pancreatic cyst fluid as a marker for evaluating malignant alternation of IPMN. Cystic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…The reported sensitivity was 10.0%, the specificity 100.0%, the positive predicted value 100.0%, the negative predicted value 85.2%, and the overall diagnostic accuracy was 85.5%. Similarly, Shirakami Y. et al described a panel of six miRNA enriched in IPMN with invasive carcinoma when compared with benign IPMN [ 83 ].…”
Section: New Perspectivesmentioning
confidence: 99%
“…The reported sensitivity was 10.0%, the specificity 100.0%, the positive predicted value 100.0%, the negative predicted value 85.2%, and the overall diagnostic accuracy was 85.5%. Similarly, Shirakami Y. et al described a panel of six miRNA enriched in IPMN with invasive carcinoma when compared with benign IPMN [ 83 ].…”
Section: New Perspectivesmentioning
confidence: 99%
“…Approximately 80% of IPMNs show high expression for microRNAs-miR-155 and miR-21. The expression of these microRNAs is particularly noticeable in advanced IPMNs and has been investigated as a potential diagnostic approach in pancreatic cyst fluid as a marker for evaluating the malignant transformation of IPMNs (Shirakami et al, 2021).…”
Section: Genetic Alterationsmentioning
confidence: 99%
“…In a further study, six miRNAs were detected at significantly higher levels in cyst fluid from IPMC than in cyst fluid from IPMA. They included miR-711, miR-3679-5p, miR-6126, miR-6780b-5p, miR-6798-5p, and miR-6879-5p, differing notably from the above group, perhaps due to the small sample size [ 64 ]. Wang et al identified miRNAs that have decreased malignant cyst fluid contents compared with benign cysts (miR-451a and miR-4284) [ 65 ].…”
Section: Microrna Expression In Patients With Cystic Pancreatic Lesio...mentioning
confidence: 99%